A digital signature system. - Kamel Arrifin, Muhammad Rezal; Abu, Nor Azman (2010)

(untitled)
The present invention provides an apparatus and method for the creation of a digital signature by utilizing public key asymmetric encryption that utilizes private keys with a minimum length of 128 bits. In one aspect the present invention provides a method and apparatus for a digital signature system that is based on a mathematically chaotic dynamic model that is digitized comprising the steps of: a recipient (12) receiving from a sender (11) a set of digital signature components (hA, sA, IDA) generated by the sender (11) together with a digital document to be sent to the recipient (12), to enable the recipient (12) to verify that the digital signature components do indeed originate from the sender (11), the recipient (12) receiving from a certificate authority (14) a validated public key certificate which contains the public key eA, of the sender (11); and the recipient (12) generating a verification key VhA from the component hA embedded within the digital signature received from the sender (11) and eA received from the certifying authority to perform verification of the senders (11) digital signature. The apparatus for key generation of the present invention comprises of a computer (1) having at least a processor (2), memory unit (3) and a key generation module (4) residing the memory unit (3).